A comparative analysis of semen quality traits and sperm kinematic parameters in relation to fertility prediction in Murrah buffaloes - Said, Syahruddin; Diansyah, Athhar Manabi; Rahayu, Johana Dian; Maulana, Tulus; Gunawan, Muhammad; Kaiin, Ekayanti Mulyawati (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The study aims to identify the most reliable fertility indicators, contributing to the development of more precise and effective evaluation protocols for Murrah buffalo breeding programs. Materials and Methods: This study analyzed 120 cryopreserved semen samples from four Murrah buffaloes. Each sample underwent quality evaluation, and sperm kinematics were analyzed using computer-assisted semen analysis. Analysis of variance was used to compare sperm quality between different bull IDs. Pearson's correlation was used to measure the correlation between each parameter. Result: The statistical analysis indicated that the motility of sperm from bull M001 was markedly reduced (p < 0.05) relative to bull M003. Likewise, the viability of sperm in M001 was significantly diminished (p < 0.05) compared to other bulls. The mitochondrial membrane potential in sperm from M004 was significantly elevated (p < 0.05) over that of M003. Furthermore, membrane integrity in M004 sperm showed a significant increase (p < 0.05) compared to M001. Kinematic measurements for buffalo M003 exhibited significantly greater (p < 0.05) values than those of M002. A strong inverse correlation (r = – 0.972) was identified between sperm quality and kinematic variables through statistical analysis, particularly involving linearity and DNA fragmentation, with significance confirmed at p < 0.05. Conclusion: The sperm quality of Murrah buffalo differs among the four buffaloes examined, particularly regarding sperm motility, viability, and energy potential. Among kinematic parameters, only velocity average path showed significant variation. The study also revealed a relationship between sperm with more linear movement and better DNA integrity. J. Adv. Vet. Anim. Res., 12(3): 751–759, September 2025 http://doi.org/10.5455/javar.2025.l938